Piperacillin/tazobactam resistance in a clinical isolate of Escherichia colidue to IS26-mediated amplification of blaTEM-1B. Issue 5 (27th May 2022) - Hubbard, Alasdair; Mason, Jenifer; Roberts, Paul; Parry, Christopher; Corless, Caroline; Aartsen, John van; Howard, Alex; Bulgasim, Issra; Fraser, Alice; Adams, Emily; Roberts, Adam; Edwards, Thomas
Abstract : We identified a clinical isolate of Escherichia coli displaying an unusual, emerging phenotype; piperacillin/tazobactam (TZP)-resistant, 3rd generation cephalosporin-susceptible. Prior to treatment with TZP, a TZP-susceptible E. coli isolate was isolated from the same patient. Hyperproduction of a class A β-lactamase has previously been linked to this phenotype, but the mechanism of hyperproduction in isolates lacking promoter region mutations is not well understood. Clonality of the two isolates was initially assessed with RFLP, and β-lactamase activity was determined using a nitrocefin assay. Both isolates were sequenced on Illumina and Oxford Nanopore Technology platforms and fitness assessed competitively. A plasmid construct containing the insertion sequence IS26was used to capture a translocatable unit (TU) in vitro. The two E. coli clinical isolates were confirmed to be clonal, with the TZP-resistant isolate hyperproducing blaTEM-1. However, no promoter region mutations were identified in the TZP-resistant isolate. Hybrid assembly revealed that an ~11kb segment of DNA was excised from a IS26 flanked pseudo-compound transposon in the TZP-resistant isolate, forming a circular TU containing blaTEM-1. Multiple re-insertion events of the TU, mediated by IS26, led to tandem repeats of the TU within the chromosome, increasing the copy number of blaTEM-1. Excision and insertion events were confirmed via capture of the TU. Amplification of the TU in the TZP-resistant isolate incurred no significant change in fitness in different environmental conditions. This study improves the understanding of the TZP-resistant, 3rd generation cephalosporin-susceptible phenotype in E. coli and antimicrobial resistance prediction of this phenotype from genotypic data.